Application Of The Level Of Community Satisfaction With Services At The Education Office Of The District Of North Bengkulu Using The Csi (Customer Satisfaction Index) - Deddy Pertan Sagala; Jusuf Wahyudi; Jhoanne Fredricka (Penerbit Jurnal Indonesia, 2024)
The North Bengkulu Regency Education Office is one of the government agencies in North Bengkulu Regency, Bengkulu Province. So far, the process of evaluating the serkvices of each employee at the Education Office of North Bengkulu Regency is still carried out internally without the views of the community. This certainly cannot be used fully in knowing the level of service satisfaction. The application of the level of public satisfaction with services at the North Bengkulu Regency Education Office using the CSI (Customer Satisfication Index) Method can assist the admin in managing the results of the service satisfaction assessment survey at the North Bengkulu Regency Education Office and provide information on the results of the public satisfaction assessment survey on the services provided. In addition, the application can also facilitate the community in providing an assessment of satisfaction with services at the North Bengkulu Regency Education Office.The application of the level of public satisfaction with services at the North Bengkulu Regency Education Office using the CSI (Customer Satisfication Index) Method is made with the PHP programming language and MySQL database. Based on system testing that has been carried out, it can be concluded that the application of the level of public satisfaction with services at the North Bengkulu Regency Education Office has run well and can be able to provide information in the form of the level of public satisfaction with services at the North Bengkulu Regency Education Office through the stages of the CSI (Customer Satisfication Index) Method.